Muscle mitochondrial catalase expression prevents neuromuscular junction disruption, atrophy, and weakness in a mouse model of accelerated sarcopenia. Issue 6 (24th September 2021) - Xu, Hongyang; Ranjit, Rojina; Richardson, Arlan; Van Remmen, Holly
Abstract: Background: Oxidative stress and damage are associated with a number of ageing phenotypes, including age‐related loss of muscle mass and reduced contractile function (sarcopenia). Our group and others have reported loss of neuromuscular junction (NMJ) integrity and increased denervation as initiating factors in sarcopenia, leading to mitochondrial dysfunction, generation of reactive oxygen species and peroxides, and loss of muscle mass and weakness. Previous studies from our laboratory show that denervation‐induced skeletal muscle mitochondrial peroxide generation is highly correlated to muscle atrophy. Here, we directly test the impact of scavenging muscle mitochondrial hydrogen peroxide on the structure and function of the NMJ and muscle mass and function in a mouse model of denervation‐induced muscle atrophy CuZnSOD ( Sod1 −/− mice, Sod1 KO). Methods: Whole‐body Sod1 KO mice were crossed to mice with increased expression of human catalase (MCAT) targeted specifically to mitochondria in skeletal muscle (mMCAT mice) to determine the impact of reduced hydrogen peroxide levels on key targets of sarcopenia, including mitochondrial function, NMJ structure and function, and indices of muscle mass and function. Results: Female adult ( 12‐month‐old) Sod1 KO mice show a number of sarcopenia‐related phenotypes in skeletal muscle including reduced mitochondrial oxygen consumption and elevated reactive oxygen species generation, fragmentation, and loss of innervated NMJs ( P < 0.05), a 30% reduction in muscle mass ( P < 0.05), a 36% loss of force generation ( P < 0.05), and a loss of exercise capacity (305 vs. 709 m in wild‐type mice, P < 0.05). Muscle from Sod1 KO mice also shows a 35% reduction in sarco(endo)plasmic reticulum ATPase activity ( P < 0.05), changes in the amount of calcium‐regulating proteins, and altered fibre‐type composition. In contrast, increased catalase expression in the mMCAT × Sod1 KO mice completely prevents the mitochondrial and NMJ‐related phenotypes and maintains muscle mass and force generation. The reduction in exercise capacity is also partially inhibited ( 35%, P < 0.05), and the loss of fibre cross‐sectional area is inhibited by 50% ( P < 0.05). Conclusions: Together, these striking findings suggest that scavenging of mitochondrial peroxide generation by mMCAT expression efficiently prevents mitochondrial dysfunction and NMJ disruption associated with denervation‐induced atrophy and weakness, supporting mitochondrial H2 O2 as an important effector of NMJ alterations that lead to phenotypes associated with sarcopenia.